THE USE OF MICROGREEN PLANTS IN NOVI SAD RESTAURANT KITCHENS: KNOWLEDGE AND EXPERIENCE OF THE EMPLOYEES - Šmugović, Stefan; Ivanović, Velibor; Kalenjuk Pivarski, Bojana; Čugalj, Milana; Trivunović, Boris (The Business of Tourism, 2024)
The hospitality industry today strives for innovation and creativity, and one of the trends that has attracted attention is the use of microgreens in professional kitchens. Microgreens, young plants with exceptionally high nutrient content, are becoming increasingly popular ingredients, making their use one of the key competitive advantages of many restaurants. The aim of this paper is to explore the knowledge and experiences of employees in the hospitality kitchens of Novi Sad regarding the use and understanding of microgreens. The research involved a survey of 150 employees working in Novi Sad’s hospitality kitchens, and the results showed that, although there is basic knowledge of the benefits of using microgreens and familiarity with their application, practical implementation varies and is generally not at a high level. This paper provides insight into current practices and potential directions for future improvement in the use of microgreens in Novi Sad’s gastronomy.